Knowledge, attitude and practice of pharmacovigilance among medical professionals at a tertiary care hospital in Mumbai, Maharashtra, India - Katekhaye, Vijay M.; Kadhe, Neha G.; John, James; Pawar, Sudhir R. (International Journal of Research in Medical Sciences, 2016)
Background: Many adverse drug reactions (ADRs), interactions and specific toxicities are known once drug is exposed to a larger population. Spontaneous reporting adverse events (AEs) are fundamental to a robust pharmacovigilance (PhV). Increasing physician awareness about the pharmacovigilance and ADR reporting can significantly contribute the safety of medicines. Objective of the study was to assess the knowledge, attitude and practices related to PhV among medical professionals at a tertiary care teaching hospital. Methods: Postgraduate students (PGs) and medical teachers at a Medical College and tertiary care hospital were evaluated for their knowledge, attitude and practice of pharmacovigilance with the help of a structured questionnaire. Suggestions for improving the effectiveness of the pharmacovigilance practices were also sought. Results: One-hundred and fifty doctors [91 (60.7%) PGs and 59 (39.3%) medical teachers] participated. Overall, 48.7% were males. 96% believed that PhV is important in medical practice but only 79.3% knew the definition of pharmacovigilance. Only 24.7% were aware of the existing nationwide pharmacovigilance program whereas the international collaborating center was known to 26% of the participants. 96% believed that it is the duty of a treating physician to report an ADR while 36.7% felt that ADR reporting should be the responsibility of a separate team. Surprisingly, 54% felt that financial aid should be provided for ADR reporting. 42.7% have not reported any ADR whilst only 16% have reported more than 10 ADRs in their career. To create an ADR database (79.3%) was the common expectation from the PhV center. 98.7% suggested continued medical education (CME) and trainings to improve the effectiveness of PhV in Indian setting. Conclusions: Regardless of a fair attitude towards PhV, the practice of ADR reporting is poor probably because of lack of sufficient knowledge about PhV. Motivating the physicians through CMEs and trainings so as to improve and strengthen the pharmacovigilance practices is the current need in India.